ONYESONWU’S RESISTANCE AGAINST RACIAL AND GENDER OPPRESSION IN NNEDI OKORAFOR’S WHO FEARS DEATH: A POSTCOLONIAL-FEMINIST CRITICISM - THERESIA COSTA RICA P., 121411223003 (2017)
Oppression has been widely known as one of social phenomena persisting since a long time ago. The issue of oppression continues to be discussed in various fields of knowledge, including Literature. Nnedi Okorafor’s novel, Who Fears Death, is among the examples. The novel raises an issue of double oppression experienced by women, especially the main character, Onyesonwu. Portrayed as a mixed-race young woman living in the future Third World country of Sudan, she is racially and sexually oppressed. In order to analyze Onyesonwu’s experience as a victim of racial and gender oppression, the theory of Postcolonial Feminism is applied in this study. This is a qualitative research which data is taken from the novel, journal articles, and other appropriate resources in conducting the analysis. This study shows that as a Third World woman, Onyesonwu rejects double oppression─racial and gender oppression─she experiences by attempting to learn higher education, rejecting male violence both from the patriarchal society of her own and the colonizer’s, and going on a quest to the West where the colonizer lives to fight against them.